Why do we age? The main signs of aging - Ugіs Kletnieks; Audrius Butkevichius; V. V. Hladyshev; S. S. Sоkolovskyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
Aging is a gradual and irreversible pathophysiological process. This is manifested in the decline of tissue and cell functions and a significant variety of pathologies associated with aging, including neurodegenerative diseases, cardiovascular diseases, metabolic disorders, increased risk of diseases of the skeleton and the immune system. Although modern medical advances have made a certain contribution to human health and greatly extended life expectancy, along with the aging of society, various chronic diseases are gradually emerging, which are the most important causes of disability and death of the elderly.